Tekoá Pyay: território de luta e resistência Guarani no Jaraguá (SP) - Souza, Nathalia Lucas Tavares de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study is to discuss the mythical relationship of ethnic territory from the context of Guarani indigenous villages - Tekoá Ytu and Tekoá Pyau; and thus contribute to the reflection of indigenous issues in Brazil, because it involves an area of permanent preservation, urban growth and traditional occupation of original right. It adopts husserliniana conception on phenomenology to evaluate the subject and nature interaction, as well as of its reproduction and reassertion in the social space which not departs from its relationship with the territory. The research identifies the main problems involving the Jaragua (SP) area regarding the Guarani population and how they remain in a limited space area, and managed to keep their old traditions in inhospitable conditions, comparing the legal mechanisms which govern the right of possession over land in Brazil. Nevertheless, provides the unique context of the Tekoá Pyau Indian village, smaller indigenous area in Brazil, which faces repossession actions, forbidding use of the Parque Estadual do Jaraguá area, a forest reserve of Atlantic Forest, but still, they set in the geographical space assigning it all the cultural and ethnic meaning

O objetivo desta pesquisa é discutir a relação mítica de território étnico a partir do contexto das aldeias indígenas Guarani - Tekoá Ytu e Tekoá Pyau. Contribui de maneira salutar a reflexão da questão indígena no Brasil, pois envolve uma área de preservação permanente, expansão urbana e ocupação tradicional de direito originário. Adota concepção husserliniana na fenomenologia para avaliação da interação sujeito e natureza, bem como, de sua reprodução e reafirmação no espaço social que não o afasta da sua relação com o território. A pesquisa identifica os principais problemas que envolvem a área do Jaraguá (SP) com relação a população Guarani e como estes permanecem em área de espaço exíguo, conseguindo manter seus costumes e tradicionais em condições inóspitas, confrontando os dispositivos legais que regem o direito de posse sobrea terra no Brasil. Não obstante, traz o quadro exclusivo da aldeia indígena Tekoá Pyau, menor área indígena do Brasil que enfrenta ações de reintegração de posse, proibição de uso da área do Parque Estadual do Jaraguá, reserva florestal de Mata Atlântica, mas que ainda assim, firmam-se no espaço geográfico atribuindo lhe toda efetividade cultural e étnica
Keywords: Human geography - Brazil; Geografia humana - Brasil; Reservas indígenas; Territorialidade humana; Conflitos étnicos; Indios Guarani; Parque Estadual do Jaraguá (SP)